Kajian Potensi dan Strategi Pengembangan Kolam Renang Tirta Randik sebagai Destinasi Pariwisata Lokal - Tri Wahyu Ningsih; Hartati; Meirizal Usra; Wahyu Indra Bayu; Herri Yusfi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Tirta Randik Swimming Pool possesses potential as a local tourism destination yet remains underutilized due to limited attraction innovation and digital promotion. This study aims to analyze potential and formulate sport-based tourism destination development strategies in Musi Banyuasin Regency. The research employed a mixed-methods approach with 4A analysis and quantitative SWOT through IFAS-EFAS matrices. Data were collected through observations, interviews, and questionnaires from 50 respondents. Results indicate attraction scored 3.32 (excellent), accessibility 3.18 (good), amenities 3.07 (good), and ancillary services 2.95 (good). SWOT analysis generated IFAS score 2.70 and EFAS score 2.57, positioning the destination in Quadrant I (aggressive strategy). Development strategies include strengthening facility quality, diversifying water tourism attractions, optimizing digital marketing, and empowering local communities to enhance sustainable competitiveness. Keywords: 4A Components, Development Strategy, Sport Tourism, Tourism Potential, Quantitative SWOT